First passenger train of the White Pass & Yukon Railroad crossing the east fork of Skagway River en route to the summit of White Pass, Alaska, February 20, 1899. - Hegg, Eric A., 1867-1948 (1899)
Shows train stopped on a trestle bridge. Caption on image: "First passenger train over White Pass and Yukon Route to summit of White Pass. Feb 20, 1899. Crossing East fork of Skaguay River" Original image in Hegg Album 2, page 32.